Design of a pressure modulator using fast-acting bistable valves. (April 2021) - Henderson, L; Cebon, D
Fast-acting pneumatic valves, combined with a slip-control braking algorithm, have recently been used to improve the straight-line braking performance of an experimental heavy goods vehicle, on low friction roads, by 16%. This paper describes how the fast-acting valves, which were central to the aforementioned research, were designed for use on a commercial vehicle. Design equations, as well as a generalized design method, are first presented for the fast-acting bistable pneumatic valve. A pressure observer is developed to predict the brake chamber pressure in cases where a pressure transducer is mounted upstream. A simple fault detection algorithm is then introduced, which utilizes some of the calculations made in the pressure observer, and is shown to correctly identify faults on a real vehicle. Performance comparisons are made between the new modulator and a conventional heavy goods vehicle electro-pneumatic brake system. Closed-loop frequency response tests show that the control bandwidth of brake chamber pressure on a heavy goods vehicle can be increased from 1.5 Hz to 10 Hz using the new hardware.